Cosplay, reality or fiction Abstract - Brenner Galarza, Gloria Cecilia (2014)
This essay reflects on fashion and the adolescents’ attitude towards the Cosplay subculture, which is spread by the media and has influence on the recipients depending on personal and social factors and the understanding of messages. Such fashion is adopted by individuals who find being part of such phenomena gratifying (Uses and Gratifications theory). Cosplay was born in Japan in the 70s and became popular in our country with globalization. It introduces many customs on clothes or habits or attitudes. Adolescents dress up like manga, anime,comics or video games characters.